Trust in E-commerce and its impact on the purchase intention of consumers in south africa - Esther, Mufhadi Thilimbilu (University of the Witwatersrand, Johannesburg, 2024)
The COVID-19 pandemic brought many challenges to companies. With the restrictions that were imposed, companies were forced to look at their digital transformation strategy to first overcome the challenges they were facing and second to determine what digital technologies could be leveraged to fast-track services and service delivery to their consumers. This research study seeks to understand the role of online trust in stimulating the purchase intention of e-commerce consumers in the South African market. The study applied an experimental research design to address the research questions. Data was collected using a structured questionnaire collected through an online survey. Data was analysed using descriptive statistics and inferential statistics (chi- squared test). Furthermore, to investigate the relationship between privacy concerns and online trust in e-commerce consumers in South Africa, regression analysis was applied, and a p-value of 0.05 was used. The SPSS Version 28 was used to analyse the data. Results show that online shopping occurs predominantly amongst youth between 18 and 39 years old with an honours degree education. Most of the participants purchase online for convenience (27.9%), and 2.6% of participants mentioned fear of cybercrime as the reason for not using online shopping. Perceived risk influences consumers’ decision-making processes for buying products on e-commerce platforms. Most of the participants learned about online shopping from social media platforms (32.5%) and 11.3% from word of mouth. Most of the participants trust the e-commerce (75%). The majority of participants mentioned that website safety and ease of navigation (95%) encourage them to purchase online. Also, 90% of participants believe that familiarity with the website before making an actual purchase reduces the risk of shopping online. This study recommended providing more online shopping platforms to youth and educated consumers since this group is more aware of the risk factors associated with online shopping.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Cybersecurity; e-commerce; Electronic word of mouth; Privacy concerns; Perceived risk; Purchase intention; Trust; SDG-8: Decent work and economic growth